Proteomics and Genomics: An Awesome Diversity in the Periodontal World - Rashmita Nayak1 , Rinkee Mohanty2 , Anurag Satapathy1 , Abhaya C Das3 , Manoj Kumar3 , Gatha Mohanty (Indian Journal of Forensic Medicine & Toxicology, 2020)
Proteins are the base structure for both the microorganisms as well as for the periodontal tissue. Theperiodontitis complex array is chiefly built by the cascade of a myriad of protein molecules. Hence, thescience as well as the study of the complex molecule proteins as biomarkers in the periodontal world,has brought into the main focus since. This complex protein is the main factor in the development of thepathogenesis of periodontitis. Thereby, it is very much used as a diagnostic biomarker. The sound andrich facts of many proteins concerned in oral pathogenesis can be applied in the analysis, avoidance andmanagement of periodontal disease. Hence, this review topic has been considered to understand the basicsof the role of Proteomics and Genomics in the field of Periodontology.